‘Inherited Images’: the Decolonialist agenda of Katherine Anne Porter and Anita Benner - Tabitha A. MORGAN (E-REA)
Katherine Anne Porter and Anita Brenner engaged transcultural journeys in order to realize their visions of validating the work of Indigenous Mexican artists. They both believed that the Indigenismo movement, made popular by the muralists in 1920s post-revolutionary Mexico, celebrated the Natives without negotiating their harsh lived reality. Porter and Brenner employed what may be termed a decolonialist agenda when they chose to work with and showcase Indigenous art in their own creative endeavors. This decolonialist agenda situated the Indigenous voice in the forefront and helped further advance a working-class aesthetic and modern Mexican identity uniquely tied to indigeneity that was often neglected by other revolutionary efforts.